2015
DOI: 10.4314/star.v3i4.5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Land use on Selected Physicochemical Properties of Soils of Gindeberet Area, Western Oromia, Ethiopia

Abstract: Article InformationThis study was carried out with the objective of determining impact of land uses on selected soil physicochemical properties of Gindeberet area, Western Ethiopia. Disturbed and undisturbed surface soil samples (0-20 cm) were collected from each land use type and examined for their analysis of soils physicochemical properties. Soil samples were analyzed at Ambo University Chemistry Laboratory. Standard procedures were employed for the analyses of selected soil properties. Soil pH ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…The lower bulk density under natural and mixed forest land use compared to others could be related to the higher organic matter content which increases the soil volume without affecting its weight. This is a result that is similar to findings in Takele et al (2015) and Fantaw and Abdu (2011). They reported that the lower bulk density in the soil under forest and the higher bulk density in soils under cultivated land were attributed to the differences in soil organic matter and less disturbances under forest land use than in the cultivated land.…”
Section: Soil Bulk Densitysupporting
confidence: 80%
“…The lower bulk density under natural and mixed forest land use compared to others could be related to the higher organic matter content which increases the soil volume without affecting its weight. This is a result that is similar to findings in Takele et al (2015) and Fantaw and Abdu (2011). They reported that the lower bulk density in the soil under forest and the higher bulk density in soils under cultivated land were attributed to the differences in soil organic matter and less disturbances under forest land use than in the cultivated land.…”
Section: Soil Bulk Densitysupporting
confidence: 80%
“…The low clay in cultivated land's surface layers could be attributed to erosion removing clay off the surface selectively, meaning that cultivated land is more prone to erosion than nearby forest and grazing fields. Similarly, Lechisa et al, (2014) found that clay was the textural class of all land use types (Table 1), indicating that the parent material was identical. Clay content, on the other hand, varied greatly depending on the land use type.…”
Section: Soil Texturementioning
confidence: 73%
“…There was no application of fertilizer use in the area, which could have influenced the pH of the soils. However, soil pH was found to be significantly changed across land use types by Lechisa et al, (2014). The pH of the soil varies from 5.65 to 4.88 depending on the land use type.…”
Section: Soil Phmentioning
confidence: 97%
See 2 more Smart Citations